2018
DOI: 10.4274/cayd.71463
|View full text |Cite
|
Sign up to set email alerts
|

Factors that Affect Prognosis and Morbidity in Pediatric Patients with Carbon Monoxide Poisoning

Abstract: Carbonmonoxide poisoning continues to be a major health problem worldwide, especially in developing countries, and constitutes an important part of the patients admitted to the pediatric emergency clinics due to poisoning. The aim of this study was to evaluate the correlation between clinical severity, morbidity, hospital stay, intensive care need, and full systemic effects in patients who were followed up and treated for carbon monoxide poisoning in our pediatric emergency clinic. Methods: The study was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
2
2
0
Order By: Relevance
“…In our country, gas cylinder or gas-fired water heaters used in baths and coal stoves are reported to be among the main causes of accidental CO poisoning. 12 , 13 In line with the results found in our study, the importance of raising awareness with intermittent warnings and trainings should be emphasized in our country where the use of wood-coal stoves is common.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In our country, gas cylinder or gas-fired water heaters used in baths and coal stoves are reported to be among the main causes of accidental CO poisoning. 12 , 13 In line with the results found in our study, the importance of raising awareness with intermittent warnings and trainings should be emphasized in our country where the use of wood-coal stoves is common.…”
Section: Discussionsupporting
confidence: 83%
“…Although there are studies reporting that there is no relationship between clinical status of patients at the time of admission and COHb levels, 8 , 18 there are also articles reporting that COHb level is related to severity of clinical signs. 12 , 14 In our study, a significant correlation was found between the presence of blurred vision, syncope, seizure, altered consciousness, weakness, confusion, restlessness, or pathological neurological examination and HBOT. Moon et al 14 evaluated the presence of neurological symptoms as an indicator of severe CO intoxication and reported COHb levels to be significantly higher in patients who presented with lethargy and confusion.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…13,24 There have been a few studies performed to demonstrate the positive contribution of ECG and routine cardiac markers (CK, CKMB) in the diagnosis of carbon monoxide-induced myocardial injury; however, findings on whether it is clinically useful are still uncertain. 17,[25][26][27][28] The total CK, Troponin-T/I, CK-MB level begin to rise 4-6 hours after the onset of the myocardial damage which is the most crucial time period for patients with carbon monoxide poisoning. 20,26,27 This may be the best explanation for not using the conventional tests since good time management with earlier detection of carbon monoxide-induced myocardial injury improves the outcome.…”
Section: Discussionmentioning
confidence: 99%